Implementation of Behavioristic Learning Theory in Language Learning - Eka Yulianti (International Journal of Education, Information Technology, and Others, 2023)
This research is a literature study using a qualitative approach. This study aims to describe behavioristic learning theory and its implementation in learning Indonesian. The data in this study were collected as analytic descriptive data. The author collects information from various references in the form of books and other written sources that are relevant to the problems studied. Behavioristic learning theory is oriented towards measurable and observable results. Repetition and training are used so that these behaviors can become habits in behavior. The expected result of the application of behavioristic learning theory is the formation of a highly desirable behavior. The behavior that gets positive reinforcement and inappropriate behavior gets negative rewards and the evaluation or final result is based on a behavior that is seen or shown